Romancing God : evangelical women and inspirational fiction - Neal, Lynn S. (University of North Carolina Press, 2006)
In the world of the evangelical romance novel, sex and desire are mitigated by an omnipresent third party, the divine. This book states that women's interpretations demonstrate the constant negotiations that characterize evangelical living. It shows the aesthetic sensibility to help alter conventional understandings, both secular and religious.